β-Caryophyllene, A Natural Dietary CB2 Receptor Selective Cannabinoid can be a Candidate to Target the Trinity of Infection, Immunity, and Inflammation in COVID-19 - Jha, Niraj Kumar; Sharma, Charu; Hashiesh, Hebaallah Mamdouh; Arunachalam, Seenipandi; Meeran, MF Nagoor; Javed, Hayate; Patil, Chandragouda R.; Goyal, Sameer N.; Ojha, Shreesh (Frontiers in Pharmacology, 2021)
Coronavirus disease (COVID-19) caused by novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an ongoing pandemic and presents a public health emergency. It has affected millions of people and continues to affect more, despite the tremendous social preventive measures. Identifying candidate drugs for the prevention and treatment of COVID-19 is crucial. The pathogenesis and the complications advanced with infection mainly involve an immune-inflammatory cascade. Therefore, the therapeutic strategy relies on suppressing infectivity and inflammation, along with immune modulation. One of the most promising therapeutic targets for modulation of immune-inflammatory responses is the endocannabinoid system, particularly the activation of cannabinoid type 2 receptors, a G-protein coupled receptor which mediates the anti-inflammatory properties by modulating numerous signaling pathways. To pharmacologically activate the CB2 receptors, a naturally occurring cannabinoid ligand, beta-caryophyllene (BCP), received attention due to its potent anti-inflammatory, antiviral, and immunomodulatory properties. BCP is recognized as a full selective functional agonist on CB2 receptors and produces therapeutic effects by activating CB2 and the nuclear receptors, PPARs. BCP is distinctively regarded as the first dietary cannabinoid with abundant presence across cannabis, as well as non-cannabis plants, including spice and other edible plants. BCP showed tissue protective properties and favorably modulates numerous signaling pathways and inhibits inflammatory mediators, including cytokines, chemokines, adhesion molecules, prostanoids, and eicosanoids. Based on the pharmacological properties, molecular mechanisms and therapeutic potential of BCP as an immunomodulator, anti-inflammatory, organprotective, and antiviral, we hypothesize that BCP could be a promising therapeutic and/or preventive candidate to target the triad of infection, immunity, and inflammation in COVID-19. In line with numerous studies proposed the potential of cannabinoids in COVID-19, BCP may be a novel candidate compound for pharmaceutical and nutraceutical development due to their unique functional receptor selectivity, wide availability and accessibility, dietary bioavailability, nonpsychoactivity, and negligible toxicity along with druggable properties, including favorable pharmacokinetic and physicochemical properties. Based on reasonable pharmacological mechanisms and therapeutic properties, we speculate that BCP has potential to be investigated against COVID-19 and will inspires further preclinical and clinical studies.